1987
DOI: 10.1289/ehp.877271
|View full text |Cite
|
Sign up to set email alerts
|

Two-hour methyl isocyanate inhalation exposure and 91-day recovery: a preliminary description of pathologic changes in F344 rats.

Abstract: The accidental release of methyl isocyanate (MIC) in Bhopal, India, was reportedly responsible for the deaths of more than 2,000 people. To study the pathology of acute inhalation exposure to MIC, the tissues of male and female Fischer 344 rats were evaluated immediately after a single 2-hr exposure to 0, 3, 10, or 30 ppm MIC, and through day 91. Early gross pathologic changes in the 30 ppm-exposed rats included a reddish white encrustation around the mouth and nose, a small thymus, and distension of the gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…This exposure pattern was chosen to mimic in duration and result the December 3, 1984, release of methyl isocyanate from a storage tank at an agricultural chemical plant in Bhopal, India. The results of this study (1)(2)(3) demonstrated that the lung and upper respiratory tract were the primary targets of methyl isocyanate injury and suggested that damage to the respiratory tract was severe enough to account for the observed mortality. Results of the previous study also demonstrated a very steep dose response for lethality of inhaled methyl isocyanate, with concentrations of 10 ppm causing few or no deaths in rats or mice, but concentrations of 20 to 30 ppm being lethal to 60 to 80% of exposed animals.…”
Section: Introductionmentioning
confidence: 70%
“…This exposure pattern was chosen to mimic in duration and result the December 3, 1984, release of methyl isocyanate from a storage tank at an agricultural chemical plant in Bhopal, India. The results of this study (1)(2)(3) demonstrated that the lung and upper respiratory tract were the primary targets of methyl isocyanate injury and suggested that damage to the respiratory tract was severe enough to account for the observed mortality. Results of the previous study also demonstrated a very steep dose response for lethality of inhaled methyl isocyanate, with concentrations of 10 ppm causing few or no deaths in rats or mice, but concentrations of 20 to 30 ppm being lethal to 60 to 80% of exposed animals.…”
Section: Introductionmentioning
confidence: 70%
“…Changes in absolute organ weights and in organ- to-body weight ratios for brain, liver, kidney, spleen, and testis (not shown) were statistically significant at certain time points in certain experimental groups, but the differences were not consistent between groups, and did not suggest a selective toxicity to any of these organs. With the exception of mild cytoplasmic vacuolization of the liver in mice, significant pathologic changes were not found in these organs (6,7). However, changes in lung-and thymus-to-body weight ratios were consistent and were dose-related in mice and rats.…”
Section: Body and Organ Weightsmentioning
confidence: 85%
“…Within 3 hr following the exposures (day 0), and again on days 1, 3, 7, 14, 49 and 91 after exposure, five predesignated animals per group were killed by pentobarbital overdose and given a complete gross necropsy. The lungs, brain, liver, kidney, thymus, testis, and spleen were weighed prior to fixation for histopathologic analysis [see accompanying papers (6,7)]. The right apical lobe of the lung was removed from male rats killed on days 0, 1, 3 and 7, weighed, and allowed to dry to constant weight for determination of wet-to-dry weight ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to these concentrations resulted in a severe necrotizing effect on the olfactory and respiratory epithelium lining the respiratory tract; no effect was observed in those areas of the nose lined with stratified squamous epithelium (9). Stratified squamous epithelium also covers the anterior portion of the cornea, and the apparent lower sensitivity of this cell type to MIC-induced damage may account at least in part for our negative findings.…”
Section: Discussionmentioning
confidence: 65%